Gut microbiota: The key to the treatment of metabolic syndrome in traditional Chinese medicine – a case study of diabetes and nonalcoholic fatty liver disease - Bao, Yang; Han, Xiao; Liu, Da; Tan, Zhaolin; Deng, Yongzhi (Frontiers in Immunology, 2022)
Metabolic syndrome mainly includes obesity, type 2 diabetes mellitus (T2DM), alcoholic fatty liver disease (NAFLD) and cardiovascular disease. As an important part of complementary and alternative medicine, traditional Chinese medicine (TCM) has been attached great importance because of its small toxic and side effects, rapid onset of effect and unique therapy of "treating different diseases together". However, due to the complexity of TCM components and the doubts about TCM treatment theory, there are still doubts about the mechanism of its function. Intestinal microbe is an important part of the human body environment, which is involved in the occurrence and development of diseases.In recent years, an increasing number of TCM studies have made the GI microbiota a new frontier for understanding and treating diseases. Nonalcoholic fatty liver disease and diabetes often occur together as twins. Our aim was to elucidate the mechanism by which the GI microbiota interacts with TCM and TCM formulations to achieve therapeutic effects on diabetes and nonalcoholic fatty liver disease. The results of the interaction between a variety of single drugs and traditional Chinese medicine formulations and intestinal tract indicate that traditional Chinese medicine may treat these two diseases by affecting the composition of intestinal microorganisms, regulating the metabolism of intestinal microorganisms, and transforming traditional Chinese medicine compounds.